(untitled) (Research, Society and Development, 2020)
The objective of this study was to perform the drying kinetics of fruit physalis, verifying the fit of the empirical mathematical models to the experimental data obtained and to evaluate the influence of the different temperatures used in the process in relation to its centesimal composition and bioactive compounds. Drying kinetics were performed using a fixed air velocity convective dryer (1.5 m.s-1) and temperature ranging from 40 to 70 °C. In fresh and dehydrated fruits, moisture content, ash, lipids, protein, total carbohydrates, anthocyanins, flavonoids, total carotenoids, total phenolic compounds and antioxidant activity (ABTS+ and DPPH) were determined. Among the studied mathematical models, the Silva et ali. model presented the best fit to the experimental data, with coefficient of determination (R2> 0.99) and chi-square values (<0.003753), being considered as most efficient in describing the physalis drying process. From the obtained data it was verified that the increase of the temperature causes reduction in the moisture, ash and lipid content, also causing the greatest degradation of all bioactive compounds analyzed (anthocyanins, flavonoids, total carotenoids, phenolic compounds) and antioxidant activity. However, temperatures of 40 and 50 °C provided better preservation of all bioactive components and antioxidant activity when compared to the values obtained for the fresh fruit.